Pelatihan Pembuatan Pestisida Nabati sebagai Solusi Pengendalian Hama dan Penyakit Tanaman Cabai di Desa Panduman Kecamatan Jelbuk Kabupaten Jember - Khowatini, Husnul; Maulida, Zulfa; Rahayu, Puji; Utami, Ratih Apri (Universitas Mataram, 2023)
Panduman Village has abundant natural resource potential, fertile land, and the majority of people work as farmers, thus supporting this village as one of the contributors to agricultural products in the form of chili commodities in Jember Regency. The productivity of chilies (Capsicum annum L.) often experiences a decline in productivity due to attacks by pests such as thrips, whitefly (Bemisia tabaci), and yellow virus or Pepper Yellow Leaf Curl Indonesia Virus (PYLCIV). Alternative control that can be carried out by farmers is the application of vegetable pesticides, which are not only economical and easy to obtain, but can also reduce pest resistance rates and chemical residues. The methods used in this activity are socialization, training and evaluation which are carried out in the form of pretest-posttest. The result was that 100% of participants understood the material and training that had been provided and were interested in and supported the sustainability of this training programs.